Pengaruh Celebrity Endorsement terhadap Purchase Decision pada Emina Indonesia - arifin, gita lestari (Journal of Business Management Education (JBME), 2020)
Abstarct: This study aims to obtain (1) an overview of celebrity endorsement, (2) a description of purchase decision, and (3) the magnitude of the influence of celebrity endorsement on purchase decision. The design of this study was cross sectional method using a descriptive and verification type approach, namely by exposing the related variables to test the relationship or influence which then formed conclusions. The object of research that is the dependent variable is purchase decision (Y) and celebrity endorsement (X). The population in this study were Abel Cantika's Instagram followers, amounting to 785,000. The method used is purposive sampling with a sample size of 108 respondents with characteristics (1) Female teenager, (2) Respondents who have liked Abel Cantika's post, and (3) Respondents who have bought Emina products. The data analysis technique used is path analysis. The findings of this study show that the picture of celebrity endorsement is in a good category. celebrity endorsement has a significant influence on purchase decision